Worker personality: Another skill bias beyond education in the digital age - Eckhardt Bode; Stephan Brunow; Ingrid Ott; Alina Sorgner (Friedrich Schiller University Jena, 2016)
We present empirical evidence suggesting that technological progress in the digital age will be biased not only with respect to skills acquired through education but also with respect to noncognitive skills (personality). We measure the direction of technological change by estimated future digitalization probabilities of occupations, and noncognitive skills by the Big Five personality traits from several German worker surveys. Even though we control extensively for education and experience, we find that workers characterized by strong openness and emotional stability tend to be less susceptible to digitalization. Traditional indicators of human capital thus measure workers' skill endowments only imperfectly.
Keywords: C25; J24; O33; 330; digital transformation; direction of technical change; Germany; noncognitive skills; worker personality